2016
DOI: 10.1016/j.cemconcomp.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of heat and mass transport during hydration of Portland cement mortar in semi-adiabatic and steam curing conditions

Abstract: A model that describes hydration and heat-mass transport in Portland cement mortar during steam curing was developed. The hydration reactions are described by a maturity function that uses the equivalent age concept, coupled to a heat and mass balance. The thermal conductivity and specific heat of mortar with water-to-cement mass ratio of 0.30 was measured during hydration, using the Transient Plane Source method. The parameters for the maturity equation and the activation energy were obtained by isothermal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…The components of the specific system of equations solved in the current study are shown in Table 3. The model consists of two ordinary differential equations that describe the equivalent time and the degree of maturity of the material (Equations 2 and 3) [11,16]. The maturity equation (Equation 3), is obtained by derivation using the chain rule; the divergence term is zero.…”
Section: Hydration Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The components of the specific system of equations solved in the current study are shown in Table 3. The model consists of two ordinary differential equations that describe the equivalent time and the degree of maturity of the material (Equations 2 and 3) [11,16]. The maturity equation (Equation 3), is obtained by derivation using the chain rule; the divergence term is zero.…”
Section: Hydration Modelmentioning
confidence: 99%
“…In order to predict these phenomena and determine curing conditions and mixture proportions that would avoid or minimize cracking, the aim of this work is to numerically simulate the moisture content, temperature, and degree of hydration during steam curing at atmospheric pressure of mortar specimens and in an AASHTO type VI beam with w/c of 0.30 and 0.45. The model previously developed by Hernández-Bautista et al [11,12] is used as the basis and compared to experimental results obtained from nuclear magnetic resonance/magnetic resonance imaging (NMR), loss on ignition (LOI), and Fourier Transform Infrared (FTIR) spectroscopy tests.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies on the heat of hydration of mass concrete began in the 1930s with the construction of the Hoover Dam in the United States. After nearly a century of development, many studies have been conducted on the thermal cracks control regarding cement type [7], concrete type [8]- [10], curing methods [11], mixing ratios [12], and admixtures [13], etc. on the heat of hydration of concrete [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the study, a WUFI 6.0 simulation model was employed, which did not consider the effect of self-desiccation and which has significant influence on the initial relative humidity level in concrete panels with relatively low w / b < 0.5. We are studying moisture behavior of the concrete structure including concrete hydration and the effect of hydration process on diffusivity in a simulation model based on previous studies (Di Luzio and Cusatis, 2009; Hernandez-Bautista et al, 2016; Sekki and Karvinen, 2017). The aim of this study is to evaluate relative humidity distribution in the concrete panel wall with different external thermal insulation materials and interior finishing materials by simulation based on practical schedule and climate conditions of the building site.…”
Section: Introductionmentioning
confidence: 99%